STUDI EKSPERIMENTAL PEMBERIAN TEGANGAN AWAL PADA DINDING BATAKO TANPA PLESTER DAN TANPA PEREKAT (BTPTP) DALAM MENERIMA BEBAN - Firmansyah, Iman; Matheus, Patrick; Purwanto, Purwanto; Sabdono, Parang (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Before the development of the framework structure (using beams and columns), loadbearing wall structure with loads that will work on the building structure bestowed on the walls commonly used in the community. One form loadbearing wall structure is commonly used arrangement brick wall. Adobe is a brick made by printing and maintaining in a damp atmosphere, tras mix, lime and water with or without other additives. One brick technology that has been developed is the use of brick without plaster and adhesives. The composition brick wall has a good ability in resisting axial forces but weak in resisting lateral forces. One of the solutions used to improve the ability of the composition of the brick wall is the lateral force resist giving the initial prestressing force (prestressed) through fastening reinforcement (via tightening bolts). Prediction failure of brick wall composition into focus the problem in this research. Experimental testing in the laboratory, carried out to see the damage that occurs in the form of brick walls in receiving loads (axial and axial-lateral). Abaqus (Simulia 6.10.1) Explicit is used as validation in predicting the form of failure that occurs in the composition of the brick Wall which receives load.